2017
DOI: 10.1016/j.jid.2016.07.036
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Filaggrin Level May Lead to Sweat Duct Obstruction in Filaggrin Mutant Mice

Abstract: tion of b-catenin does not increase dermal papilla cell number in the hair follicle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…47 The decreased levels of KRT77 in STS of patients with AD identified in our study and significant negative correlation with TEWL may suggest previously unrecognized decreased eccrine sweat glands density in AD skin. Of interest, reduced sweat production, sweat glands obstruction, and abnormalities in sweat gland morphology have been found in the footpads of Flg mutant mice as compared to wild-type mice, 50 also suggesting a potential regulation of sweat glands by Flg. Our data demonstrate a significant positive correlation between KRT77 levels in STS and levels of FLG in the same skin site as determined by FLG breakdown products PCA and UCA.…”
Section: Discussionmentioning
confidence: 99%
“…47 The decreased levels of KRT77 in STS of patients with AD identified in our study and significant negative correlation with TEWL may suggest previously unrecognized decreased eccrine sweat glands density in AD skin. Of interest, reduced sweat production, sweat glands obstruction, and abnormalities in sweat gland morphology have been found in the footpads of Flg mutant mice as compared to wild-type mice, 50 also suggesting a potential regulation of sweat glands by Flg. Our data demonstrate a significant positive correlation between KRT77 levels in STS and levels of FLG in the same skin site as determined by FLG breakdown products PCA and UCA.…”
Section: Discussionmentioning
confidence: 99%
“…67 These inconsistent results indicated that the dysfunction of sweat glands and delivery system might play a role in AD. 72 The studies on filaggrin mutant mice demonstrate that decreased filaggrin levels lead to acrosyringium obstruction and eventually gives rise to sweating impairment, 73 which could indirectly affect dermcidin activity.…”
Section: Cathelicidinsmentioning
confidence: 99%
“…Sweat contributes to the functioning of the cutaneous barrier and shapes the cutaneous microbiome. Impairment of sweating along with reduced levels of dermcidin, an antimicrobial peptide specific for sweat, has been reported in atopics, but the available data on this remain controversial. Thus, new methods to approach and measure “sweating,” sweat glands and ducts to assess the contribution of “sweat” to AD pathogenesis are important and are expected to evolve so that stratification of patients with AD into “sweaters” and sweating‐impaired subgroups can be accomplished.…”
Section: In Vivo Monitoring Of Ad and The Search For “Good” Ad Biomarmentioning
confidence: 99%